Level and Trend of Child Health and Nutrition Status in Nepal: Evidence from Demographic and Health Survey (1996-2016) - Timsina, Drishti; Chowhan, Rushel; Sharma, Sharad Kumar (Journal of Nepal Health Research Council, 2023)
Background: Child health and nutrition are key indicators of the country’s socioeconomic development and quality of life. The purpose of the paper was to examine the level, trend, and socio-demographic differences of selected child health and nutrition indicators and to provide policy recommendations for improvement. Methods: Desk review was conducted to compile secondary information on child health and nutrition status published in the Nepal Demographic and Health Survey reports prepared by Ministry of Health and Population from 1996 to 2016. Trend lines, bar diagram, and GIS maps were prepared to study and present the findings. Results: A substantial decrease in under-five mortality, from 118 to 39 (67% point decline) and neonatal mortality, from 50 to 21 (58% point decline) deaths per 1000 live births, was noted between 1996 and 2016. Full immunization coverage decreased from 87% in 2011 to 78% in 2016. 36% of children under the age of five were stunted, 25% were underweight, and 10% were wasted in 2016. Boys were more likely to receive treatment for diarrhoea (72%), compared to girls (56%). The majority of the children (74%) had their acute respiratory infections managed at private medical centers. Child health and nutritional status differed by geographic regions, being better in Gandaki and Bagmati and poor in Karnali and Madesh. Overall health and nutrition status of children were better among educated, and wealthier families. Conclusions: To further reduce childhood mortality and reach the targets for the Sustainable Development Goal, targeted interventions must be implemented to improve immunization coverage plus health and nutritional status among disadvantaged populations. Keywords: Child health; child mortality; Nepal; nutritional status